Infrared-absorbing fiber and textile product
By combining composite tungsten oxide particles and Group 5 element composite oxide particles in infrared absorbing fibers, the challenge of achieving neutral color tones while maintaining infrared absorption is addressed, resulting in fibers with improved heat retention and color neutrality.
Patent Information
- Application Number
- JP2023153869
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
Existing infrared absorbing fibers containing composite tungsten oxide particles tend to absorb long wavelength light, resulting in a blue color tone, making it difficult to achieve neutral or complementary colors.
Incorporating both composite tungsten oxide particles and Group 5 element composite oxide particles into the fibers, which allows for simultaneous infrared absorption and neutral color appearance by adjusting the concentration of these particles.
The fibers achieve effective infrared absorption while suppressing blue tones, enabling the production of neutral-colored textile products with enhanced heat retention properties.
Smart Images

Figure 2025045863000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an infrared absorbing fiber and a textile product. [Background technology]
[0002] Various cold weather clothing, interior decorations, and leisure items with improved thermal insulation have been devised and put to practical use. There are two main methods for improving thermal insulation.
[0003] The first method is to physically increase the number of air spaces in the cold weather clothing, for example by controlling the woven or knitted structure of the clothing or by making the fibers used hollow or porous, thereby reducing the dissipation of heat generated by the human body and maintaining heat retention.
[0004] The second method, for example in the case of cold-weather clothing, is to apply chemical or physical processing to the entire garment or to the fibers that make up the garment. The second method is to improve the warmth retention by actively storing heat inside the garment, such as by radiating the heat generated by the human body back to the human body or by converting part of the sunlight received by the garment into heat.
[0005] Specific methods for implementing the first method described above have included increasing the amount of air space in the clothing, making the fabric thicker, making the weave finer, or making the color darker.
[0006] For example, clothing used in winter, such as sweaters, corresponds to clothing using the first method. Also, for example, in clothing that has been commonly used for winter sports clothing using the first method, padding is placed between the outer and inner layers, and the thickness of the air layer in the padding maintains heat retention. However, when padding is placed inside the clothing, the clothing becomes heavy and bulky, which causes problems when used for sports that require ease of movement.
[0007] In order to solve these problems, the second method mentioned above, which actively and effectively utilizes heat generated by the human body inside the clothing and heat from sunlight and the like from outside the clothing, has begun to be adopted in recent years.
[0008] One specific method for implementing the second method is to form a metal-vapor-deposited surface by evaporating a metal such as aluminum or titanium onto the lining of clothing, and to actively prevent the dissipation of heat by reflecting the radiant heat emitted from the human body onto the metal-vapor-deposited surface. However, the method of forming a metal-vapor-deposited surface on clothing not only requires costs for evaporating the metal onto the clothing, but also leads to poor yields due to uneven deposition, which ultimately leads to an increase in the price of the product itself.
[0009] As another specific method for implementing the second method, a method has been proposed in which ceramic particles such as alumina, zirconia, magnesia, etc. are kneaded into the fibers and the far-infrared radiation effect and the effect of converting light into heat that the ceramic particles have are utilized, that is, a method in which external energy is actively taken in.
[0010] For example, Patent Document 1 states that the thermal conductivity is 0.3 Kcal / m 2 The document describes a heat-radiating fiber that contains one or more kinds of inorganic fine particles having heat-radiating properties, which contain at least one of metals and metal ions with a thermal conductivity of 1.0 sec·° C. or more. Silica or barium sulfate is cited as the inorganic fine particles having heat-radiating properties.
[0011] Patent Document 2 describes a heat-retaining composite fiber comprising a thermoplastic polymer A having a melting point of 110°C or higher and a thermoplastic polymer B having a melting point of 15 to 50°C, a cooling crystallization temperature of 40°C or lower, and a heat of crystallization of 10 mJ / mg or higher, the fiber containing 0.1 to 20% by weight of ceramic microparticles having far-infrared radiation capability relative to the fiber weight, and the fiber surface being covered with polymer A.
[0012] Patent Document 3 describes an infrared absorbing processed textile product obtained by dispersing and fixing in a textile product a binder resin containing an infrared absorbing agent made of at least one amino compound represented by a specific general formula.
[0013] Patent Document 4 describes a near-infrared absorbing processing method for a cellulosic fiber structure in which a dye selected from direct dyes, reactive dyes, naphthol dyes, and vat dyes, which has greater absorption in the near-infrared region than black dyes, is combined with other dyes to achieve a near-infrared absorption level of 65% or less in the spectral reflectance of the fabric within the range of 750 to 1500 nm.
[0014] In Patent Documents 5 to 7, the applicant of the present application has selected tungsten oxide microparticles and / or composite tungsten oxide microparticles as materials that have high transmittance and low absorbance for visible light but low transmittance and high absorbance for light in the near-infrared region, and has proposed fibers containing these microparticles as near-infrared absorbing components, and textile products made by processing the fibers. Although the above-mentioned fibers and textile products are light-colored, they absorb the near-infrared rays of sunlight and convert them into heat, have moisture retention, and are highly designable because they can be colored in various colors by adding other pigments. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] Japanese Patent Application Publication No. 11-279830 [Patent Document 2] Japanese Patent Application Publication No. 5-239716 [Patent Document 3] Japanese Patent Application Publication No. 8-003870 [Patent Document 4] Japanese Patent Application Publication No. 9-291463 [Patent Document 5] JP 2006-132042 A [Patent Document 6] International Publication No. 2018 / 235839 [Patent Document 7] International Publication No. 2019 / 054476 Summary of the Invention [Problem to be solved by the invention]
[0016] The tungsten oxide microparticles and composite tungsten oxide microparticles disclosed in Patent Documents 5 to 7 are materials that have high transmittance and low absorptance of visible light, but low transmittance and high absorptance of infrared light. For this reason, fibers containing composite tungsten oxide microparticles and the like are particularly promising fibers for applications such as cold weather clothing.
[0017] However, the composite tungsten oxide microparticles, etc., preferentially absorb long-wavelength light, i.e., red light, among visible light, and are therefore colored blue, and the degree of blueness increases with the amount of composite tungsten oxide microparticles, etc. added. Therefore, fibers containing composite tungsten oxide microparticles, etc. as infrared absorbing components, and textile products obtained by processing such fibers, are colored blue, and it may be difficult to color them by adding other pigments to yellow, which is the complementary color of blue, or light colors other than blue. Therefore, there has been a demand for fibers that contain composite tungsten oxide with excellent infrared absorbing properties and can be colored to a more neutral color tone that can be colored to a complementary color or light color.
[0018] Therefore, one aspect of the present invention has an object to provide an infrared absorbing fiber that contains infrared absorbing particles containing a composite tungsten oxide and can have a neutral color tone. [Means for solving the problem]
[0019] In one aspect of the invention, a fiber and Infrared absorbing particles, The infrared absorbing particles provide an infrared absorbing fiber, which contains at least composite tungsten oxide particles and Group 5 element composite oxide particles. Effect of the Invention
[0020] In one aspect of the present invention, there is provided an infrared absorbing fiber that includes infrared absorbing particles containing a composite tungsten oxide and can have a neutral color tone. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is an explanatory diagram of the hexagonal crystal structure of composite tungsten oxide. [Diagram 2] FIG. 2 is an explanatory diagram of the structure of an infrared absorbing fiber. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, the form for carrying out the present invention will be described with reference to the drawings. However, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment without departing from the scope of the present invention.
[0023] An infrared absorbing fiber according to one embodiment of the present disclosure (hereinafter referred to as "the present embodiment") includes fibers and infrared absorbing particles.
[0024] The infrared absorbing particles contained in the infrared absorbing fiber of this embodiment contain at least both composite tungsten oxide particles and Group 5 element composite oxide particles. The infrared absorbing particles may be composed only of composite tungsten oxide particles and Group 5 element composite oxide particles.
[0025] The present inventors have conducted various studies in order to obtain an infrared absorbing fiber that contains infrared absorbing particles containing a composite tungsten oxide and can have a neutral color tone.
[0026] In this specification, the term "neutral color tone" means that the blue color tone can be suppressed. For this reason, when the infrared absorbing fiber does not contain a colorant material for adjusting the color tone other than the composite tungsten oxide particles and the Group 5 element composite oxide particles, the infrared absorbing fiber has a neutral color tone as defined in JIS Z 8729 (2004). * a * b * In color coordinates, b * This means that the value will be -3.0 or greater.
[0027] For example, if one only wishes to reduce the blue color tone resulting from the composite tungsten oxide particles, it may be sufficient to reduce the concentration (content) of the composite tungsten oxide particles in the fibers.
[0028] However, when the concentration of the composite tungsten oxide particles is reduced, the infrared absorbing ability is also reduced at the same time, which results in a significant reduction in the intended effect of absorbing infrared rays from sunlight and converting them into heat.
[0029] Also, for example, if it is only necessary to reduce the blue color tone, it is possible to simply use a general colored pigment or dye in combination with the composite tungsten oxide particles in the fiber to adjust the color to reduce the blue color. However, general colored pigments and dyes do not have the ability to absorb infrared rays. Therefore, although it is possible to adjust the color by absorbing a part of visible light, it is not possible to expect infrared absorption ability.
[0030] On the other hand, the inventor of the present invention has invented a Group 5 element composite oxide particle having a specific composition as a novel infrared absorbing particle. The infrared absorbing particle has high transparency in the visible light region, has an infrared absorbing effect, and has optical properties and color tone different from conventional materials such as composite tungsten oxide. However, when the visible light absorbing ability is fixed, the infrared absorbing ability is lower than that of conventional composite tungsten oxide particles.
[0031] In the course of the inventors' study of the present invention, they came up with a completely new idea of manufacturing infrared-absorbing fibers by using composite tungsten oxide particles and group 5 element composite oxides in combination instead of using them separately. The infrared-absorbing fibers obtained by combining composite tungsten oxide particles and group 5 element composite oxides have distinct advantages in that they can simultaneously achieve an infrared absorption effect and a neutral color tone appearance. As a result, it was found that the infrared-absorbing fibers can achieve optical properties with high industrial utility value that simultaneously meet the above-described infrared absorption effect and the user's need for a more neutral color tone, and the present invention was thus completed.
[0032] Hereinafter, embodiments of the present invention will be described in the order of [a] composite tungsten oxide particles, [b] method for producing group 5 element composite oxide particles and group 5 element composite oxides, [c] infrared-absorbing particle dispersion liquid, [d] infrared-absorbing fibers, and [e] method for producing infrared-absorbing fibers. [a] Composite tungsten oxide particles (Regarding the composition) As the composite tungsten oxide particles, particles containing a composite tungsten oxide represented by the general formula: M x WO 3-y can be preferably used. Note that the composite tungsten oxide particles can be composed only of the composite tungsten oxide represented by the above general formula, but it does not exclude the inclusion of inevitable impurities.
[0033] However, in the above general formula, M represents element M, W represents tungsten, and O represents oxygen.
[0034] Element M is preferably at least one element selected from K (potassium), Rb (rubidium), Cs (cesium), and Tl (thallium).
[0035] Also, x and y in the above general formula are preferably 0.15 ≦ x ≦ 0.33 and 0 < y ≦ 0.46.
[0036] The composite tungsten oxide particles have infrared absorption characteristics. Therefore, by containing the composite tungsten oxide particles, the infrared absorption particles can suppress the transmission of light in the infrared region, particularly in the near-infrared region, and can exhibit infrared absorption ability. Further, since the absorption coefficient of light in the visible light region is very small compared to the absorption coefficient of light in the infrared region, high transparency can be maintained for light in the visible light region even when the transmission of light in the infrared region is sufficiently suppressed.
[0037] The composite tungsten oxide is represented by the general formula: M x WO 3-y as described above, and has a composition in which the element M is added to tungsten oxide (WO 3-y ).
[0038] According to the studies of the inventors of the present invention, tungsten oxide (WO 3-y ) also has infrared absorption characteristics. However, in the case of tungsten oxide, since there are no effective free electrons in tungsten trioxide (WO3), the absorption and reflection characteristics in the near-infrared region are small. However, by making y, which is the amount of oxygen deficiency with respect to tungsten in tungsten oxide (WO 3-y ), greater than 0, free electrons can be generated in the tungsten oxide, and efficient infrared absorption particles can be obtained. However, the crystal phase of WO2 may cause absorption and scattering of light in the visible light region and reduce the absorption of light in the near-infrared region. Therefore, in the case of tungsten oxide particles, by satisfying 0 < y ≦ 0.46 for y in the general formula represented by WO 3-y , the generation of the crystal phase of WO2 can be suppressed, and efficient infrared absorption particles can be obtained.
[0039] And in the case of composite tungsten oxide particles used as infrared absorption particles, by adding the element M to tungsten oxide, free electrons are generated in the composite tungsten oxide, and stronger absorption characteristics derived from free electrons are exhibited in the infrared region. Therefore, the composite tungsten oxide particles exhibit particularly high characteristics as an infrared absorption material that absorbs infrared rays.
[0040] Regarding composite tungsten oxides, by combining the control of the amount of oxygen deficiency described in tungsten oxides and the addition of element M that generates free electrons, a more efficient infrared absorption material can be obtained. When the control of the amount of oxygen deficiency and the addition of element M that generates free electrons are combined, the general formula for the composite tungsten oxide: M x WO 3-y In, it is preferable to satisfy the relationship of 0.15 ≦ x ≦ 0.33, 0 < y ≦ 0.46.
[0041] The value of x indicating the addition amount of element M in the general formula of the composite tungsten oxide will be described. When the value of x is 0.15 or more, a sufficient amount of free electrons is generated, and since the desired near-infrared absorption effect can be obtained, it is preferable. Also, if the value of x is 0.33 or less, it is preferable because the generation of an impurity phase in the composite tungsten oxide particles can be avoided.
[0042] Next, the value of y indicating the amount of oxygen deficiency will be described. General formula: M x WO 3-y In the composite tungsten oxide represented by, the same mechanism as in the case of the value of y in the above-described tungsten oxide (WO 3-y ) works. For this reason, it is preferable that y satisfies 0 < y ≦ 0.46.
[0043] The crystal structure of the composite tungsten oxide contained in the composite tungsten oxide particles is not particularly limited, and a composite tungsten oxide having any crystal structure can be contained. However, when the composite tungsten oxide contained in the composite tungsten oxide particles has a hexagonal crystal structure, the transmittance of light in the visible light region and the absorption of light in the infrared region of the composite tungsten oxide particles are particularly improved, which is preferable.
[0044] A schematic plan view of the hexagonal crystal structure is shown in FIG. 1. FIG. 1 shows a view of the crystal structure of the composite tungsten oxide having a hexagonal crystal structure as seen from the (001) direction, and the unit lattice 10 is shown by a dotted line.
[0045] In Fig. 1, six octahedrons 11 formed of WO6 units are assembled to form a hexagonal cross-sectional cavity (tunnel) 12. The six octahedrons 11 and an element M 13 arranged in the cavity 12 form one unit (unit structure), and a large number of these units are assembled to form a hexagonal crystal structure.
[0046] In this way, when the composite tungsten oxide particle contains the composite tungsten oxide containing the above-mentioned unit structure, it can particularly improve the transmittance of light in the visible light region and the absorption of light in the infrared region.It is not necessary that the entire composite tungsten oxide particle is composed of the crystalline composite tungsten oxide particle having the structure shown in Figure 1, and for example, even if it has the relevant structure locally, it can obtain the effect of improving the transmittance of light in the visible light region and the absorption of light in the infrared region.Therefore, the composite tungsten oxide particle as a whole may be crystalline or amorphous.
[0047] The above-mentioned hexagonal crystal is easily formed when an element M having a large ionic radius is added as the element M of the composite tungsten oxide. Specifically, the hexagonal crystal is easily formed when, for example, one or more of K, Rb, Cs, and Tl are added as the element M. For this reason, it is preferable that the element M includes one or more selected from K, Rb, Cs, and Tl, and it is more preferable that the element M is one or more selected from K, Rb, Cs, and Tl.
[0048] When the element M includes one or more selected from Cs and Rb, the composite tungsten oxide is particularly likely to form a hexagonal crystal. Therefore, it is more preferable that the composite tungsten oxide includes one or more selected from Cs and Rb as the element M. In addition, the composite tungsten oxide may include one or more selected from Cs and Rb as the element M. In particular, when the element M includes Cs, the weather resistance of the composite tungsten oxide is increased, so it is particularly preferable that the element M includes Cs.
[0049] In order for a hexagonal crystal to be formed, it is sufficient that element M is present in the hexagonal gaps formed by the WO6 units, and it is not limited to the above elements being added as element M.
[0050] In addition, the composite tungsten oxide contained in composite tungsten oxide particles can have the structure of tetragonal or cubic tungsten bronze other than the above-mentioned hexagonal crystal, and the composite tungsten oxide of this structure is also effective as infrared absorbing material.That is, the composite tungsten oxide contained in the composite tungsten oxide particles contained in infrared absorbing particles is not limited to the composite tungsten oxide of hexagonal crystal, and the composite tungsten of tetragonal crystal or cubic crystal can also be suitably used.
[0051] The absorption position (absorption wavelength) of infrared light in composite tungsten oxide tends to change depending on its crystal structure. For example, the absorption position of infrared light tends to move to the longer wavelength side in tetragonal crystals than in cubic crystals, and furthermore, in hexagonal crystals, it tends to move to the longer wavelength side than in tetragonal crystals. In addition, accompanying the change in the absorption position of light due to the above crystal structure, the absorption of light in the visible light region is the smallest in hexagonal crystals, followed by tetragonal crystals, and among these, the absorption of light in the visible light region is the largest in cubic crystals. That is, in the composite tungsten oxide of hexagonal crystals, the contrast between the transmittance of light in the visible light region and the transmittance of light in the infrared region becomes large.
[0052] Therefore, when high light transmittance in the visible light region and high light absorption rate in the infrared region are particularly required, it is preferable to use hexagonal tungsten bronze. However, the tendency of the optical properties described here is merely a rough tendency, and it also changes depending on the type of element M added, the amount added, and the amount of oxygen. Therefore, the composite tungsten oxide contained in the composite tungsten oxide particle contained in the infrared absorbing particle is not limited to a hexagonal material.
[0053] The crystal structure of the composite tungsten oxide contained in the composite tungsten oxide particles is not limited to the above, and for example, the composite tungsten oxide particles may simultaneously contain composite tungsten oxides having different crystal structures.
[0054] However, as described above, the hexagonal composite tungsten oxide can increase the transmittance of light in the visible light region and the absorption of light in the infrared region. Therefore, the composite tungsten oxide particles preferably contain a composite tungsten oxide having a hexagonal crystal system, and may also be composed of a hexagonal composite tungsten oxide. (Particle characteristics of composite tungsten oxide particles) The average particle size of the composite tungsten oxide particles is not particularly limited, and can be arbitrarily selected according to the characteristics required for the infrared absorbing fiber. For example, when the infrared absorbing fiber is used for an application requiring particularly high transparency with respect to light in the visible light region, the composite tungsten oxide particles preferably have an average particle size of 100 nm or less. This is because when the average particle size of the composite tungsten oxide particles is 100 nm or less, light scattering can be suppressed, and unintended luster in the visible light region and unintended color tone due to light scattering (Rayleigh scattering) whose intensity is wavelength-dependent can be suppressed.
[0055] In this specification, the average particle size means the volume average particle size. That is, the average particle size in this specification is the average particle size weighted by the particle volume, and is obtained by multiplying the diameter of each particle by the volume of the particle in a particle collection and dividing the sum by the total volume of the particles. The volume average particle size (MV) can be measured, for example, using a particle size distribution measuring device based on the dynamic light scattering method.
[0056] In addition, if coarse particles are present in the process of kneading the infrared absorbing particles of this embodiment into fibers, the yarn may be cut during spinning. From this perspective, it is preferable to reduce the particle size of the composite tungsten oxide particles. Specifically, the volume average particle size of the composite tungsten oxide particles is more preferably 40 nm or less, even more preferably 30 nm or less, and particularly preferably 25 nm or less.
[0057] As described above, from the viewpoint of avoiding light scattering, the average particle size of composite tungsten oxide particles is preferably small. However, if the average particle size of composite tungsten oxide particles is too small, it may be difficult to handle when manufacturing infrared absorbing particle dispersion liquid, or may cause aggregation in infrared absorbing particle dispersion liquid. Therefore, the average particle size of composite tungsten oxide particles is preferably 0.1 nm or more.
[0058] For this reason, the average particle size of the composite tungsten oxide particles is preferably 0.1 nm or more and 100 nm or less, more preferably 0.1 nm or more and 40 nm or less, even more preferably 0.1 nm or more and 30 nm or less, and particularly preferably 0.1 nm or more and 25 nm or less.
[0059] The method for producing the composite tungsten oxide particles is not particularly limited, and the particles can be produced by various known methods. [b] Group 5 element composite oxide particles and method for producing group 5 element composite oxide particles [b-1] Group 5 element composite oxide particles The present inventors have conducted research into novel infrared absorbing particles. The novel infrared absorbing particles are preferably infrared absorbing particles that absorb light in the infrared region, particularly in the near infrared region.
[0060] In examining new infrared absorbing particles, the inventors of the present invention focused on oxides of Group 5 elements. However, since there are no effective free electrons or holes in the pentoxides of Group 5 elements (V2O5, Nb2O5, Ta2O5), they have little absorption and reflection characteristics in the infrared region and are not effective as infrared absorbing materials. However, when a Group 5 composite oxide is made by adding an electropositive element to the above oxide, free electrons or holes are generated in the composite oxide, and absorption characteristics derived from the free electrons or holes are expressed in the infrared region. Therefore, it was found that new infrared absorbing particles can be made.
[0061] Furthermore, the inventors of the present invention have found that there is a specific range of the composition of the complex oxide that is particularly effective as an infrared absorbing particle. Specifically, they have found that by setting the composition range of the complex oxide within a specific range, the complex oxide is transparent in the visible light region and absorbs in the infrared region. (About the composition) The Group 5 element composite oxide particles can contain a composite oxide in which an electropositive element is added to an oxide of a Group 5 element.
[0062] The composite oxide contained in the Group 5 element composite oxide particles can contain the following A1 element, A2 element, and B element.
[0063] The A1 element is one or more elements selected from H (hydrogen) and alkali metal elements.
[0064] The A2 element is one or more elements selected from Mg (magnesium) and alkaline earth metal elements.
[0065] The B element is one or more elements selected from the group consisting of V (vanadium), Nb (niobium), and Ta (tantalum).
[0066] When the amount of substance of the A1 element contained in the composite oxide is x1, the amount of substance of the A2 element is x2, and the amount of substance of the B element is y, it is preferable that the following relationships are satisfied: 0.002≦(x1+x2) / y≦1.5, 0.001≦x1≦1, and 0.001≦x2≦1.
[0067] The Group 5 element composite oxide particles may be composed only of the composite oxides described above, but even in this case, this does not exclude the case where the Group 5 element composite oxide particles contain unavoidable impurities that are mixed in during the manufacturing process, etc.
[0068] As described above, by adding electropositive elements A1 and A2 to an oxide containing B element to form the above composite oxide, infrared absorbing properties can be exhibited.
[0069] Furthermore, by simultaneously adding the A1 and A2 elements to an oxide containing the B element and setting the composition within a predetermined range, the Group 5 element composite oxide particles containing the composite oxide can have a light absorption peak in the wavelength region of 1500 nm to 2100 nm. This is thought to be because free electrons or holes with a density suitable for having a light absorption peak in the wavelength region of 1500 nm to 2100 nm are generated if the composition of the A1 and A2 elements is within the range.
[0070] As described above, the A1 element is preferably one or more elements selected from H and alkali metal elements. In this specification, the alkali metal elements refer to Li (lithium), Na (sodium), K (potassium), Rb (rubidium), Cs (cesium), and Fr (francium).
[0071] In particular, from the viewpoint of improving the stability of the composite oxide, the A1 element is preferably one or more elements selected from H, Li, Na, K, Rb, and Cs, and more preferably one or more elements selected from Na and K.
[0072] As described above, the A2 element is preferably one or more elements selected from Mg and alkaline earth metal elements. In this specification, the alkaline earth metal elements refer to Ca (calcium), Sr (strontium), Ba (barium), and Ra (radium).
[0073] In particular, from the viewpoint of improving the stability of the composite oxide, the A2 element is preferably one or more elements selected from alkaline earth metal elements, and more preferably one or more elements selected from Ca, Sr and Ba.
[0074] Furthermore, as described above, the B element can be one or more elements selected from V, Nb, and Ta, is preferably one or more elements selected from Nb and Ta, and is more preferably Nb.
[0075] By setting the value of (x1+x2) / y, which indicates the content ratio of the total amount of substance of the A1 element and the A2 element to the B element in the composite oxide, to 0.002 or more, a sufficient amount of free electrons or holes are generated in the composite oxide, and the desired infrared absorbing effect is obtained. The higher the content of the A1 element and the A2 element, the greater the supply of free electrons and the higher the infrared absorbing efficiency, but the effect is saturated when the value of (x1+x2) / y is about 1.5. In addition, if the value of (x1+x2) / y is 1.5 or less, it is possible to avoid the generation of an impurity phase in the infrared absorbing particles. For this reason, it is preferable that (x1+x2) / y satisfies the relationship of 0.002≦(x1+x2) / y≦1.5 as described above, more preferably that it satisfies the relationship of 0.5≦(x1+x2) / y≦1.0, and even more preferably that it satisfies the relationship of 0.7≦(x1+x2) / y≦1.0.
[0076] The above composite oxide is, for example, represented by the general formula A1 x1 A2 x2 B y O zIt can be expressed as follows. In the general formula, "A1" represents the A1 element, "A2" represents the A2 element, "B" represents the B element, and "O" represents oxygen. As shown by the general formula, the composite oxide is preferably composed of, for example, the A1 element, the A2 element, the B element, and oxygen.
[0077] By adding the A1 element and the A2 element to the oxide containing the B element, free electrons or holes are supplied to the composite oxide, and infrared absorption characteristics can be exhibited. Therefore, the amount of oxygen contained in the composite oxide is not particularly limited. However, by setting the oxygen amount within a predetermined range, the amount of free electrons or holes in the composite oxide can be set within a particularly preferable range from the viewpoint of enhancing the infrared absorption characteristics. Therefore, z / y corresponding to the content ratio of oxygen to the B element in the composite oxide is preferably 1.0 < z / y < 3.5, more preferably 2.0 < z / y < 3.5, still more preferably 2.0 < z / y ≤ 3.0, and most preferably 2.4 ≤ z / y ≤ 3.0.
[0078] As described above, z / y corresponds to the content ratio of oxygen to the B element in the composite oxide and is a value that affects the oxygen deficiency amount or oxygen excess amount of the composite oxide. As described above, the amount of free electrons or holes in the composite oxide can also be controlled by the amount of oxygen. Therefore, it is preferable to control the value of z / y according to the required infrared absorption characteristics and the like. The value of z / y can be easily controlled by the synthesis conditions of the Group 5 element composite oxide particles.
[0079] The above general formula A1 x1 A2 x2 B y O z In x1, x2, y, z, it is preferable to satisfy 0 < (x1 + 2x2 + 5y - 2z) / y ≤ 3, more preferably to satisfy 0 < (x1 + 2x2 + 5y - 2z) / y ≤ 2, and still more preferably to satisfy 0.1 ≤ (x1 + 2x2 + 5y - 2z) / y ≤ 1. The above (x1 + 2x2 + 5y - 2z) / y indicates a measure of the excess or deficiency of electrons per B element. When the above range is satisfied, a particularly high infrared absorption effect can be exhibited. (Crystal structure and lattice constant of complex oxides) According to the study by the inventors of the present invention, when a complex oxide has any one of the crystal structures selected from cubic, tetragonal, and orthorhombic (rectangular), the transmission of light in the visible light region is improved and the absorption of light in the infrared region is improved. However, in order to obtain the effect of improving the transmission of light in the visible light region and improving the absorption of light in the infrared region, it is sufficient that the complex oxide contains a unit structure of a cubic, tetragonal, or orthorhombic crystal structure, and the complex oxide may partially contain amorphous or other structures.
[0080] In the composite oxide, (x1+x2) / y, which indicates the content ratio of the total amount of substance of A1 element and A2 element to B element, is 1.0, and z / y, which indicates the content ratio of the amount of substance of oxygen to B element, is 3.0. In this case, the crystal structure of the composite oxide is a cubic perovskite structure. Specifically, for example, Na 0.5 Sr 0.5 NbO3, K 0.5 Ba 0.5 NbO3 etc. have a cubic perovskite structure.
[0081] A complex oxide having a basic structure of (x1+x2) / y=1.0 and z / y=3.0 may have a cubic perovskite structure with deficiencies in one or more elements selected from the A1 and A2 elements when the complex oxide has a (x1+x2) / y value of less than 1.0. A complex oxide having a z / y value of less than 3.0 may have a cubic perovskite structure with oxygen deficiencies. Furthermore, depending on the deficiency state of each element, the complex oxide may have a tetragonal, orthorhombic, or monoclinic crystal structure in which (A1, A2)BO3 blocks and BO blocks are regularly stacked. A complex oxide having a z / y value of more than 3.0 and less than 3.5 may have a cubic, tetragonal, orthorhombic crystal structure.
[0082] As infrared absorbing particles, materials that strongly absorb light in the infrared region and weakly absorb light in the visible light region are often required. However, since the required performance varies depending on the application and other factors, it is not possible to generally determine which of the above crystal structures is preferable.
[0083] For example, when the complex oxide is Na x1 Sr x2 NbO z (2.0 < z ≤ 3.0), for example, when the value of (x1 + x2) is 0.8 or more and less than 1.0, it may adopt a cubic perovskite structure having a deficiency of Na element and Sr element, and in some cases, further oxygen deficiency. Also, when the complex oxide is Na x1 Sr x2 NbO z (2.0 < z ≤ 3.0), it may have a tetragonal or orthorhombic crystal structure in which (Na, Sr)NbO3 blocks and NbO blocks are regularly stacked. In the complex oxide having the above composition and crystal structure, the heat insulation property tends to be high. Note that the heat insulation property means a property determined by the balance between visible light transparency and infrared absorption.
[0084] Thus, since the relationship between the crystal structure and the infrared absorption characteristics also changes depending on the composition of the complex oxide, the crystal structure of the complex oxide contained in the Group 5 element complex oxide particles is not particularly limited and can be selected according to the composition of the complex oxide and the required infrared absorption characteristics and the like.
[0085] The lattice constant of the complex oxide is not particularly limited, but the lattice constant of the a-axis based on the cubic perovskite structure is preferably 3.96 Å or more and 4.14 Å or less, more preferably 3.97 Å or more and 4.14 Å or less, and still more preferably 3.98 Å or more and 4.13 Å or less. The lattice constant can be calculated by Rietveld analysis.
[0086] In addition, when the crystal structure is not cubic (i.e., when it is orthorhombic, orthorhombic, etc.), the lattice constant of the a-axis when the cubic perovskite structure is used as a reference (hereinafter, may be referred to as the "pseudocubic lattice constant") can be converted from the value of the lattice constant in the crystal structure. Specifically, the composition of the unit cell of the non-cubic crystal structure is identified. Then, the unit cell volume is calculated based on the lattice constant. Next, the unit cell volume per atom of the B element is calculated. The calculated unit cell volume per atom of the B element can be converted to the pseudocubic lattice constant by taking the cube root. (Particle characteristics of Group 5 element composite oxide particles) The particle characteristics such as the average particle size of the Group 5 element composite oxide particles are not particularly limited, and can be selected arbitrarily depending on the required infrared absorption characteristics, etc.
[0087] The Group 5 element composite oxide particles preferably have an average particle size of 100 nm or less.
[0088] In general, it is known that materials containing free electrons or holes show a reflection / absorption response to infrared rays around the solar radiation range of wavelengths from 200 nm to 2600 nm due to plasma oscillation. It is also known that if powder particles of such materials are made smaller than the wavelength of light, geometric scattering in the visible light range is reduced and transparency in the visible light range is obtained.
[0089] In this specification, the term "transparency" is used to mean "high transmittance with little scattering of light in the visible light region."
[0090] Therefore, it is preferable that the Group 5 element composite oxide particles have an average particle size of 100 nm or less as measured by a particle size distribution measuring device. This is because particles with an average particle size of 100 nm or less do not completely block light due to scattering, and can maintain visibility in the visible light range while efficiently maintaining transparency at the same time. In particular, when transparency in the visible light range is important, it is preferable to further consider scattering by the particles.
[0091] When further reduction in scattering by the Group 5 element composite oxide particles is required, the average particle size is more preferably 40 nm or less, even more preferably 30 nm or less, and particularly preferably 25 nm or less. If the average particle size of the Group 5 element composite oxide particles is small, scattering of light in the visible light region due to geometric scattering or Mie scattering is reduced. Therefore, by setting the average particle size of the Group 5 element composite oxide particles within the above range, when the Group 5 element composite oxide particles are applied to infrared absorbing fibers, the influence on the color tone of the fibers can be suppressed. When the average particle size is 40 nm or less, the geometric scattering or Mie scattering is reduced, and the Rayleigh scattering region is reached. In the Rayleigh scattering region, the scattered light is proportional to the sixth power of the particle diameter, so that the scattering is reduced and the transparency is improved as the average particle size decreases.
[0092] Furthermore, if the average particle size is 30 nm or less, the scattered light is very small, which is preferable. From the viewpoint of avoiding light scattering, the smaller the average particle size, the more preferable it is. Therefore, the lower limit of the average particle size is not particularly limited, but the average particle size is preferably 0.1 nm or more. This is because an average particle size of 0.1 nm or more is easy to manufacture industrially.
[0093] As described above, the average particle size of the Group 5 element composite oxide particles is preferably 0.1 nm or more and 100 nm or less, more preferably 0.1 nm or more and 40 nm or less, even more preferably 0.1 nm or more and 30 nm or less, and particularly preferably 0.1 nm or more and 25 nm or less.
[0094] It is preferable that both the composite tungsten oxide particles and the Group 5 element composite oxide particles, or the infrared absorbing particles containing both particles, have the same particle size characteristics as the composite tungsten oxide particles and the Group 5 element composite oxide particles.
[0095] For this reason, for both the composite tungsten oxide particles and the Group 5 element composite oxide particles, and also for the infrared absorbing particles, the average particle size is preferably 0.1 nm or more and 100 nm or less, more preferably 0.1 nm or more and 40 nm or less, even more preferably 0.1 nm or more and 30 nm or less, and particularly preferably 0.1 nm or more and 25 nm or less. [b-2] Method for producing Group 5 element composite oxide particles Next, a method for producing Group 5 element composite oxide particles will be described. Since the method for producing Group 5 element composite oxide particles described below can produce the previously described Group 5 element composite oxide particles, some of the matters already described will not be described.
[0096] The Group 5 element composite oxide particles can be produced by a solid-state reaction method. When synthesizing by the solid-state reaction method, for example, an A1 element compound or an A1 element alone, an A2 element compound or an A2 element alone, and a B element compound or an B element alone can be used as raw materials.
[0097] The method for producing Group 5 element composite oxide particles can include a mixed powder preparation step (first mixed powder preparation step) of preparing a mixed powder of an A1 element compound or an A1 element alone, an A2 element compound or an A2 element alone, and a B element compound or an B element alone.
[0098] The A1 element source containing the A1 element can be an A1 element compound or an A1 element alone. The A1 element compound used as the raw material is preferably one or more selected from the group consisting of oxides, hydroxides, carbonates, nitrates, sulfates, oxalates, organic compounds, sulfides, and chlorides of the A1 element.
[0099] As the A2 element source containing the A2 element, an A2 element compound or an A2 element alone can be used. The A2 element compound as the raw material is preferably one or more selected from the group consisting of oxides, hydroxides, carbonates, nitrates, sulfates, oxalates, organic compounds, sulfides, and chlorides of the A2 element.
[0100] Since the preferred A1 and A2 elements have already been explained, the explanation will be omitted here.
[0101] The B element compound or element B, which is a source of the B element containing the B element, is preferably one or more selected from the following: pentoxides (V2O5, Nb2O5, Ta2O5), dioxides (VO2, NbO2, TaO2), sesquioxides (V2O3, Nb2O3), elemental metals (V, Nb, Ta), sulfates, ammonium salts, organic compounds, sulfides, chlorides, and oxide hydrates obtained by dissolving the chlorides in a liquid such as alcohol, adding water to hydrolyze the solution, and evaporating the solvent. Note that suitable B elements have already been described, so a description thereof will be omitted here.
[0102] In the mixed powder preparation step, the specific procedure for obtaining a mixed powder of an A1 element compound or an A1 element simple substance, an A2 element compound or an A2 element simple substance, and a B element compound or an B element simple substance is not particularly limited. For example, the A1 element compound, etc., the A2 element compound, etc., and the B element compound, etc. are dry-mixed in powder form to obtain a mixed powder. In addition, the A1 element compound, etc. can be dissolved in water, wet-mixed with the A2 element compound, etc. and the B element compound, etc., and then dried to obtain a mixed powder.
[0103] In the mixed powder preparation step, it is preferable to mix the A1 element, the A2 element, and the B element so that the ratio of the substance amount in the resulting mixed powder is the ratio of the A1 element, the A2 element, and the B element in the target composite oxide. That is, it is preferable to mix so that the ratio of the total substance amount of the A1 element and the A2 element in the target composite oxide to the substance amount (B) of the B element is satisfied, that is, (A1+A2):B=(x1+x2):y. As described above, x1, x2, and y are preferably (x1+x2) / y=0.002≦(x1+x2) / y≦1.5, more preferably 0.5≦(x1+x2) / y≦1.0, and even more preferably 0.7≦(x1+x2) / y≦1.0. For this reason, it is preferable to mix the A1 element compound, the A2 element compound, and the B element compound so that they are in the above-mentioned preferred range.
[0104] The Group 5 element composite oxide particles can be synthesized in multiple stages to obtain Group 5 element composite oxide particles containing a composite oxide of the target composition. In this case, in the first mixed powder preparation step, the A1 element compound, A2 element compound, and B element compound can be mixed to obtain the composition of the intermediate product.
[0105] The method for producing Group 5 element composite oxide particles can further include a firing step (first firing step) of firing the mixed powder obtained in the mixed powder preparation step (first mixed powder preparation step).
[0106] The conditions for the firing step are not particularly limited. In the firing step, for example, the mixed powder can be fired in any atmosphere selected from an inert gas atmosphere, a reducing gas atmosphere, a vacuum atmosphere, a mixed gas atmosphere of an inert gas and a reducing gas, and an oxidizing atmosphere containing oxygen.
[0107] For example, in the case of a composite oxide, when oxygen vacancies are introduced and z / y in the general formula described above is made smaller than the stoichiometric ratio, the firing atmosphere is preferably a mixed gas atmosphere of an inert gas and a reducing gas. The reducing gas is not particularly limited, but is preferably, for example, hydrogen gas. In addition, when hydrogen gas is used as the reducing gas, the volume ratio of hydrogen gas is preferably 1% or more, and more preferably 3% or more. The upper limit of the volume ratio of hydrogen gas is not particularly limited, and since it can be reduced gas alone, it can be up to 100%.
[0108] The inert gas is not particularly limited, but one or more types selected from nitrogen gas, rare gases, and the like can be used.
[0109] The oxidizing atmosphere may be any atmosphere containing oxygen, for example, an atmosphere containing oxygen in a volume ratio of 18% to 100%. For example, the atmosphere may be air.
[0110] The firing temperature in the firing step is not particularly limited, but the firing temperature is preferably equal to or higher than the temperature at which the generated composite oxide starts to crystallize and equal to or lower than the melting point of the composite oxide. Specifically, the firing temperature is preferably set to, for example, 1000° C. or higher and 2100° C. or lower.
[0111] The Group 5 element composite oxide particles can be synthesized in multiple stages to obtain Group 5 element composite oxide particles containing a composite oxide of a target composition. When synthesizing in multiple stages, a B element compound or a B element alone can be added and mixed with the intermediate product obtained in the above-mentioned firing step (first firing step) (second mixed powder preparation step). It is also possible to prepare multiple types of intermediate products with different compositions and mix them in the second mixed powder preparation step. In this case, a B element compound or a B element alone can be added and mixed as necessary. When preparing multiple types of intermediate products with different compositions, the above-mentioned mixed powder preparation step and firing step (first firing step) can be performed for each intermediate product.
[0112] The B element compound used in the second mixed powder preparation step is not particularly limited, but for example, the compounds already described in the first mixed powder preparation step can be used. In the second mixed powder preparation step, it is preferable to mix so that the ratio of the total amount of substance of the A1 element and the A2 element in the resulting mixed powder to the amount of substance of the B element is the ratio of the total amount of substance of the A1 element and the A2 element to the amount of substance of the B element in the target composite oxide. In other words, it is preferable to mix so as to satisfy (A1+A2):B=(x1+x2):y, which is the ratio of the total amount of substance of the A1 element and the A2 element in the target composite oxide to the amount of substance of the B element (B). The mixing can be performed in the same manner as in the mixed powder preparation step, so a description will be omitted here.
[0113] The obtained mixed powder is then subjected to a firing step (second firing step) to prepare Group 5 element composite oxide particles. The conditions for the second firing step are not particularly limited, but the firing atmosphere and firing temperature can be the same as those described for the firing step (first firing step), and therefore will not be described here. The firing conditions for the first firing step and the second firing step may be the same or different.
[0114] By carrying out the steps described above, it is possible to obtain Group 5 element composite oxide particles. After the firing step is completed, the obtained Group 5 element composite oxide particles can be crushed, pulverized, sieved, or the like, as necessary, to obtain a desired particle size distribution. [c] Infrared absorbing particle dispersion Next, a configuration example of the infrared absorbing particle dispersion liquid of this embodiment will be described.
[0115] The infrared absorbing particle dispersion liquid of this embodiment can also be used, for example, when producing infrared absorbing fibers, which will be described later.
[0116] The infrared absorbing particle dispersion liquid of this embodiment can contain infrared absorbing particles and a liquid medium which is one or more selected from water, an organic solvent, oils and fats, liquid resins, and liquid plasticizers.
[0117] The infrared absorbing particles can contain the above-mentioned composite tungsten oxide particles and Group 5 element composite oxide particles.
[0118] The infrared absorbing particle dispersion liquid preferably has a configuration in which infrared absorbing particles are dispersed in a liquid medium.
[0119] The liquid medium may be one or more selected from water, organic solvents, oils and fats, liquid resins, and liquid plasticizers.
[0120] As the organic solvent, various types can be selected, such as alcohols, ketones, hydrocarbons, and glycols. Specific examples of the solvent include alcohol solvents such as isopropyl alcohol, methanol, ethanol, 1-propanol, isopropanol, butanol, pentanol, benzyl alcohol, diacetone alcohol, and 1-methoxy-2-propanol; ketone solvents such as dimethyl ketone, acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, cyclohexanone, and isophorone; ester solvents such as 3-methyl-methoxy-propionate and butyl acetate; glycol derivatives such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol isopropyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, and propylene glycol ethyl ether acetate; amides such as formamide, N-methylformamide, dimethylformamide, dimethylacetamide, and N-methyl-2-pyrrolidone; aromatic hydrocarbons such as toluene and xylene; and halogenated hydrocarbons such as ethylene chloride and chlorobenzene.
[0121] However, among these, the organic solvent is preferably an organic solvent having a low polarity, and in particular, isopropyl alcohol, ethanol, 1-methoxy-2-propanol, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether acetate, n-butyl acetate, etc. These organic solvents can be used alone or in combination of two or more kinds.
[0122] Examples of fats and oils that can be used include one or more selected from drying oils such as linseed oil, sunflower oil, and tung oil; semi-drying oils such as sesame oil, cottonseed oil, rapeseed oil, soybean oil, and rice bran oil; non-drying oils such as olive oil, coconut oil, palm oil, and dehydrated castor oil; fatty acid monoesters obtained by directly esterifying fatty acids of vegetable oils with monoalcohols; ethers; and petroleum-based solvents such as Isopar (registered trademark) E, Exxor (registered trademark) Hexane, Heptane, E, D30, D40, D60, D80, D95, D110, and D130 (all manufactured by ExxonMobil).
[0123] As the liquid resin, for example, one or more types selected from liquid acrylic resin, liquid epoxy resin, liquid polyester resin, liquid urethane resin, and the like can be used.
[0124] As the liquid plasticizer, for example, a liquid plasticizer for plastics can be used.
[0125] The components contained in the infrared absorbing particle dispersion are not limited to the infrared absorbing particles and the liquid medium, and the infrared absorbing particle dispersion may further contain any optional components added thereto, if necessary.
[0126] For example, an acid or an alkali may be added to the infrared absorbing particle dispersion liquid as necessary to adjust the pH of the dispersion liquid.
[0127] In addition, in order to further improve the dispersion stability of the infrared absorbing particles in the above-mentioned infrared absorbing particle dispersion liquid and to prevent the dispersed particle size from becoming coarse due to re-aggregation, various surfactants, coupling agents, and the like can be added to the infrared absorbing particle dispersion liquid as dispersants.
[0128] Dispersants such as surfactants and coupling agents can be selected according to the application, but it is preferable that the dispersant has one or more functional groups selected from an amine-containing group, a hydroxyl group, a carboxyl group, and an epoxy group. These functional groups adsorb to the surface of the infrared absorbing particles to prevent aggregation, and have the effect of uniformly dispersing the infrared absorbing particles, for example, in infrared absorbing fibers formed using the infrared absorbing particles. A polymer dispersant having one or more functional groups selected from the above functional groups (functional groups) in the molecule is more preferable.
[0129] Suitable commercially available dispersants include Solsperse (registered trademark) 9000, 12000, 17000, 20000, 21000, 24000, 26000, 27000, 28000, 32000, 35100, 54000, and 250 (manufactured by Lubrizol Japan Co., Ltd.), EFKA (registered trademark) 4008, 4009, 4010, 4015, 4046, 4047, 4060, 4080, 7462, 4020, 4050 ... 055, 4400, 4401, 4402, 4403, 4300, 4320, 4330, 4340, 6220, 6225, 6700, 6780, 6782, 8503 (manufactured by F-Ka Additives), AJISPER (registered trademark) PA111, PB821, PB822, PN411, FAMEX L-12 (manufactured by Ajinomoto Fine-Techno Co., Ltd.), DisperBYK (registered trademark) 101, 102, 106, 108, 111, 116, 13 0, 140, 142, 145, 161, 162, 163, 164, 166, 167, 168, 170, 171, 174, 180, 182, 192, 193, 2000, 2001, 2020, 2025, 2050, 2070, 2155, 2164, 220S, 300, 306, 320, 322, 325, 330, 340, 350, 377, 378, 380N, 410, 425, 430 (manufactured by BYK Japan Co., Ltd.), Dis Examples of the polyurethane foam include one or more selected from Paron (registered trademark) 1751N, 1831, 1850, 1860, 1934, DA-400N, DA-703-50, DA-725, DA-705, DA-7301, DN-900, NS-5210, and NVI-8514L (manufactured by Kusumoto Chemicals Co., Ltd.), and Arphon (registered trademark) UC-3000, UF-5022, UG-4010, UG-4035, and UG-4070 (manufactured by Toagosei Co., Ltd.).
[0130] The method of dispersing infrared absorbing particles in a liquid medium is not particularly limited as long as it can disperse infrared absorbing particles in a liquid medium. In this case, it is preferable to disperse infrared absorbing particles so that the average particle size is 200 nm or less, and more preferably to disperse infrared absorbing particles so that the average particle size is 0.1 nm or more and 200 nm or less. In addition, it is preferable to disperse composite tungsten oxide particles, composite oxide particles of group 5 elements, infrared absorbing particles, etc. so that the average particle size satisfies the above-mentioned preferred range.
[0131] Examples of the dispersion method of infrared absorbing particles in a liquid medium include dispersion methods using devices such as a bead mill, a ball mill, a sand mill, a paint shaker, and an ultrasonic homogenizer. Among them, it is preferable to pulverize and disperse using a media agitation mill such as a bead mill, a ball mill, a sand mill, or a paint shaker using a media (beads, poles, Ottawa sand) from the viewpoint of shortening the time required to obtain a desired average particle size. By the pulverization-dispersion treatment using a media agitation mill, the infrared absorbing particles are dispersed in a liquid medium, and at the same time, the infrared absorbing particles are atomized due to collisions between the infrared absorbing particles and collisions of the media with the infrared absorbing particles, and the infrared absorbing particles can be further atomized and dispersed. That is, the pulverization-dispersion treatment is performed.
[0132] The infrared absorbing particle dispersion contains both composite tungsten oxide particles and Group 5 element composite oxide particles as infrared absorbing particles. Therefore, the composite tungsten oxide particles and Group 5 element composite oxide particles may be added to the same liquid medium, and both particles may be simultaneously ground and dispersed to obtain an infrared absorbing particle dispersion containing both composite tungsten oxide particles and Group 5 element composite oxide particles. Alternatively, the composite tungsten oxide particles and Group 5 element composite oxide particles may be added to liquid media individually, and each liquid medium may be individually ground and dispersed to obtain a composite tungsten oxide particle dispersion and a Group 5 element composite oxide particle dispersion. Then, the infrared absorbing particle dispersion may be obtained by thoroughly mixing these two types of dispersions.
[0133] The average particle size of the infrared absorbing particles is preferably 0.1 nm or more and 200 nm or less as described above. This is because, if the average particle size is small, scattering of light in the visible light region due to geometric scattering or Mie scattering is reduced. As a result of reducing the scattering of light by the infrared absorbing particles, it is possible to avoid the inability to obtain clear transparency in, for example, infrared absorbing fibers obtained using the infrared absorbing particle dispersion liquid of this embodiment. That is, when the average particle size is 200 nm or less, the light scattering mode of the geometric scattering or Mie scattering becomes weaker and becomes a Rayleigh scattering mode. In the Rayleigh scattering region, the scattered light is proportional to the sixth power of the dispersed particle size, so that the scattering is reduced and the transparency is improved as the dispersed particle size decreases. And, when the average particle size is 100 nm or less, the scattered light is very small, which is preferable.
[0134] Incidentally, the dispersed state of the infrared absorbing particles in the infrared absorbing particle dispersion obtained by using the infrared absorbing particle dispersion liquid of this embodiment, in which the infrared absorbing particles are dispersed in a solid medium such as a resin, does not result in aggregation greater than the average particle size of the infrared absorbing particles in the dispersion liquid, as long as a known method for adding the dispersion liquid to the solid medium is used.
[0135] The content of the infrared absorbing particles in the infrared absorbing particle dispersion of this embodiment is not particularly limited, but is preferably, for example, 0.01% by mass or more and 80% by mass or less. This is because a sufficient solar radiation absorptivity can be exhibited by making the content of the infrared absorbing particles 0.01% by mass or more. Also, by making the content 80% by mass or less, the infrared absorbing particles can be uniformly dispersed in the dispersion medium.
[0136] The "content of infrared absorbing particles in the infrared absorbing particle dispersion liquid" refers to the total content of the composite tungsten oxide particles and the Group 5 element composite oxide particles described above.
[0137] The infrared absorbing particle dispersion of this embodiment, and the infrared absorbing fibers and textile products described below can contain, as the infrared absorbing particles, the above-mentioned composite tungsten oxide particles and Group 5 element composite oxide particles in an appropriate ratio.
[0138] The infrared absorbing particle dispersion of this embodiment, as well as the infrared absorbing fiber and textile product described later, have two advantages: infrared absorbing properties and a neutral color tone with suppressed blueness. The infrared absorbing properties and color tone of the infrared absorbing particles can also be adjusted by adjusting the content ratio of the composite tungsten oxide particles and the Group 5 element composite oxide particles contained in the infrared absorbing particles. Therefore, the mixing ratio of the composite tungsten oxide particles and the Group 5 composite oxide particles can be selected according to the color tone and infrared absorbing properties required for the infrared absorbing fiber or textile product.
[0139] For example, in infrared absorbing particles, infrared absorbing particle dispersions containing infrared absorbing particles, infrared absorbing fibers, and textile products, the lower limit of the mass ratio of the composite tungsten oxide particles and the Group 5 element composite oxide particles contained in the infrared absorbing particles is preferably 100:20 or more, more preferably 100:25 or more, even more preferably 100:30 or more, and even more preferably 100:50 or more.
[0140] In other words, when the mass of the composite tungsten oxide particles in the infrared absorbing particles is taken as 100 mass%, the mass proportion of the Group 5 element composite oxide particles is preferably 20 mass% or more, more preferably 25 mass% or more, even more preferably 30 mass% or more, and particularly preferably 50 mass% or more.
[0141] In addition, the upper limit of the mass ratio of the composite tungsten oxide particles and the Group 5 element composite oxide particles contained in the infrared absorbing particles in the infrared absorbing particles, the infrared absorbing particle dispersion liquid containing the infrared absorbing particles, the infrared absorbing fiber, and the textile product is preferably 100:500 or less, more preferably 100:400 or less, and even more preferably 100:300 or less.
[0142] That is, when the mass of the composite tungsten oxide particles in the infrared absorbing particles is taken as 100 mass%, the mass proportion of the Group 5 element composite oxide particles is preferably 500 mass% or less, more preferably 400 mass% or less, and even more preferably 300 mass% or less.
[0143] The color tone of a textile product when a composite tungsten oxide particle is mixed with a composite oxide particle of a group 5 element is, for example, L defined in JIS Z 8729 (2004). * a * b * It can be evaluated by color coordinates. Specifically, when no color material (pigment, dye) for adjusting color tone is included other than the composite tungsten oxide particles and the Group 5 element composite oxide particles, * The value is preferably -3.0 or more and 10.0 or less, more preferably -2.0 or more and 4.0 or less, and even more preferably -1.0 or more and 2.0 or less. * If the value is -3.0 or more, the blueness of the textile product can be suppressed, and the degree of freedom in color tone can be increased. * If the value is 10.0 or less, the yellowing of the textile product can be suppressed, and the degree of freedom in color tone can be increased. In addition, when no color material (pigment, dye) for adjusting color tone is included other than the composite tungsten oxide particles and the Group 5 element composite oxide particles, the L * The value is preferably 80.0 or more, and more preferably 85.0 or more. * If the value is 80.0 or more, the color of the textile product can be prevented from becoming dark (gray, black), and the degree of freedom in color tone can be increased. * The value is an index expressed as a value between 0 and 100, with a smaller value indicating a darker color and a larger value indicating a lighter color. [d] Infrared absorbing fiber The infrared absorbing fiber according to this embodiment will be described.
[0144] A schematic diagram of the infrared absorbing fiber of this embodiment is shown in Fig. 2. Fig. 2 shows a schematic cross-sectional view of a plane passing through a central axis CA of a fiber 21 of an infrared absorbing fiber 20. As shown in Fig. 2, the infrared absorbing fiber 20 of this embodiment can include a fiber 21 and an infrared absorbing particle 22.
[0145] The arrangement of the infrared absorbing particles 22 is not particularly limited, and the infrared absorbing particles 22 can be arranged, for example, at one or more locations selected from the surface 21A and the interior 21B of the fiber 21. Note that FIG. 2 is a schematic diagram showing an example in which the infrared absorbing particles 22 are arranged on both the surface 21A and the interior 21B of the fiber 21, but is not limited to such a form. The infrared absorbing particles 22 may be arranged on only one of the surface 21A and the interior 21B of the fiber 21. Also, in FIG. 2, the infrared absorbing particles 22 are depicted as spherical particles, but the shape of the infrared absorbing particles 22 is not limited to such a form and can have any shape.
[0146] The infrared absorbing particles 22 may contain composite tungsten oxide particles 221 and Group 5 element composite oxide particles 222 .
[0147] Hereinafter, the components contained in the infrared absorbing fiber of this embodiment will be described. (1) Fibers (1-1) Types of fibers The fibers contained in the infrared absorbing fiber of this embodiment can be selected from various types depending on the application and are not particularly limited. For example, the fibers are preferably one or more types selected from a fiber group consisting of synthetic fibers, semi-synthetic fibers, natural fibers, regenerated fibers, and inorganic fibers, and a mixed yarn obtained by blending, doubling, or mixing two or more types of fibers selected from the above fiber group. In other words, fibers selected from the above fiber group can be used, and fibers selected from the above mixed yarn can also be used.
[0148] Among these, in consideration of the ease with which the infrared absorbing particles can be incorporated inside the fibers and the durability of heat retention, it is preferable that the fibers contain synthetic fibers, and it is more preferable that the fibers are made of synthetic fibers.
[0149] Each fiber will be described below. (1-1-1) Synthetic Fibers The synthetic fiber is not particularly limited, but for example, one or more types selected from polyurethane fibers, polyamide fibers, acrylic fibers, polyester fibers, polyolefin fibers, polyvinyl alcohol fibers, polyvinylidene chloride fibers, polyvinyl chloride fibers, polyether ester fibers, and the like can be suitably used.
[0150] Examples of polyamide fibers include nylon, nylon 6, nylon 66, nylon 11, nylon 610, nylon 612, aromatic nylon, and aramid.
[0151] Examples of acrylic fibers include polyacrylonitrile, acrylonitrile-vinyl chloride copolymer, and modacrylic.
[0152] Examples of polyester fibers include polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, and polyethylene naphthalate.
[0153] Examples of polyolefin fibers include polyethylene, polypropylene, and polystyrene.
[0154] An example of the polyvinyl alcohol fiber is vinylon.
[0155] The polyvinylidene chloride fibers include, for example, vinylidene.
[0156] The polyvinyl chloride fibers include, for example, polyvinyl chloride.
[0157] Examples of polyetherester fibers include Lexe and Success. (1-1-2) Semi-synthetic fibers The semi-synthetic fibers are preferably one or more types selected from, for example, cellulosic fibers, protein fibers, chlorinated rubber, and hydrochloric rubber.
[0158] Examples of cellulosic fibers include acetate, triacetate, and acetate oxide.
[0159] An example of a protein-based fiber is Promix. (1-1-3) Natural fibers The natural fibers are preferably one or more types selected from, for example, vegetable fibers, animal fibers, mineral fibers, and the like.
[0160] Examples of plant fibers include cotton, kapok, flax, hemp, jute, Manila hemp, sisal, New Zealand hemp, ramie, palm, rush, and wheat straw.
[0161] Examples of animal fibers include wool such as sheep's wool, goat's hair, mohair, cashmere, alpaca, angora, camel, and vicuna, as well as silk, down, and feathers.
[0162] Examples of mineral fibers include asbestos. (1-1-4) Regenerated fibers The regenerated fibers are preferably one or more types selected from, for example, cellulosic fibers, protein fibers, alginate fibers, rubber fibers, chitin fibers, mannan fibers, and the like.
[0163] Examples of cellulosic fibers include rayon, viscose rayon, cupro, polynosic, and cuprammonium rayon.
[0164] Examples of protein-based fibers include casein fiber, peanut protein fiber, corn protein fiber, soy protein fiber, and regenerated silk. (1-1-5) Inorganic fibers As the inorganic fibers, for example, one or more types selected from metal fibers, carbon fibers, silicate fibers, and the like can be used.
[0165] Examples of the metal fibers include metal fibers, gold threads, silver threads, and heat-resistant alloy fibers.
[0166] Examples of silicate fibers include glass fibers, slag fibers, and rock fibers. (1-2) Fiber shape The cross-sectional shape of the fibers is not particularly limited, and examples thereof include one or more types selected from the group consisting of circular, triangular, hollow, flat, Y-shaped, star-shaped, and core-sheath-shaped.
[0167] The inclusion and arrangement of infrared absorbing particles in the fiber is not particularly limited. For example, when the cross-sectional shape of the fiber is a core-sheath type, the infrared absorbing particles may be included in the core part of the fiber or in the sheath part. In addition, the shape of the fiber is not particularly limited, and may be a filament (long fiber) or a staple (short fiber). (2) Infrared absorbing particles As the infrared absorbing particles, the infrared absorbing particles already described can be used. Since the infrared absorbing particles have already been described, the description thereof will be omitted here.
[0168] The content of the infrared absorbing particles in the infrared absorbing fiber of this embodiment is not particularly limited, and can be selected depending on the properties required of the infrared absorbing fiber.
[0169] The infrared absorbing fiber of this embodiment preferably contains infrared absorbing particles in a proportion of 0.001% by mass or more and 80% by mass or less, and more preferably 0.005% by mass or more and 50% by mass or less, relative to the solid content of the fiber.
[0170] By including infrared absorbing particles at a ratio of 0.001% by mass or more relative to the solid content of the fiber, sufficient infrared absorbing effect can be obtained even if the fabric containing the infrared absorbing fiber is thin. Also, by including infrared absorbing particles at a ratio of 80% by mass or less relative to the solid content of the fiber, deterioration of spinnability due to clogging of the filter or thread breakage during spinning of the infrared absorbing fiber can be more reliably avoided. Also, by setting the content of infrared absorbing particles to 80% by mass or less, deterioration of the physical properties of the fiber can be more reliably avoided.
[0171] (3) Far-infrared emitting substances and additives The infrared absorbing fiber of the present embodiment may be composed only of the above-mentioned fiber and infrared absorbing particles, but may also contain any further components, for example, far-infrared emitting substances and additives described below depending on the purpose.
[0172] Incidentally, even when the infrared absorbing fiber is composed only of fibers and infrared absorbing particles as described above, this does not exclude the inclusion of unavoidable components etc. that are mixed in during the manufacturing process. (3-1) Far-infrared emitting materials The far-infrared emitting material is a material capable of emitting far-infrared rays, and is preferably in the form of particles, that is, far-infrared emitting material particles can be suitably used as the far-infrared emitting material.
[0173] The far-infrared emitting material can be disposed at one or more locations selected from the surface and the interior of the fiber.
[0174] Examples of far-infrared emitting substances include one or more selected from metal oxides such as ZrO2, SiO2, TiO2, Al2O3, MnO2, MgO, Fe2O3, and CuO; carbides such as ZrC, SiC, and TiC; and nitrides such as ZrN, Si3N4, and AlN.
[0175] An example of the composite tungsten oxide particles contained in the infrared absorbing particles is particles containing cesium tungsten oxide. Cesium tungsten oxide has the property of absorbing solar energy with a wavelength of 0.3 μm or more and 3 μm or less, and in particular selectively absorbs infrared light in the vicinity of the wavelength range of 0.9 μm or more and 2.2 μm or less, and converts it to heat or re-radiates it.
[0176] On the other hand, particles of far-infrared emitting material have the ability to receive the energy absorbed by cesium tungsten oxide, an infrared absorbing material, convert the energy into thermal energy of mid- to far-infrared wavelengths, and radiate it. For example, ZrO2 particles convert this energy into thermal energy with a wavelength of 2 μm to 20 μm, and radiate it. Therefore, by coexisting the far-infrared emitting material capable of radiating far-infrared rays and the above-mentioned infrared absorbing particles inside or on the surface of the fiber, the solar energy absorbed by the infrared absorbing particles is efficiently consumed inside or on the surface of the fiber, and more effective heat retention is achieved.
[0177] The content of the far-infrared emitting substance in the infrared absorbing fiber is not particularly limited, and can be selected depending on the performance required of the infrared absorbing fiber.
[0178] The infrared absorbing fiber of the present embodiment preferably contains the far-infrared emitting substance in a proportion of, for example, 0.001% by mass or more and 80% by mass or less relative to the solid content of the fiber.
[0179] This is because, by setting the content of the far-infrared emitting material to 0.001% by mass or more, a sufficient thermal energy radiation effect can be obtained even if the fabric containing the infrared absorbing fiber is thin, and, by setting the content of the far-infrared emitting material to 80% by mass or less, deterioration of spinnability due to clogging of the filter, thread breakage, etc. during spinning of the infrared absorbing fiber can be more reliably avoided. (3-2) Additives Examples of additives include antioxidants, flame retardants, deodorants, insect repellents, antibacterial agents, ultraviolet absorbers, etc. The additives can be contained and used within the range that does not impair the performance of the infrared absorbing fiber. [e] Manufacturing method for infrared absorbing fiber The method for producing the infrared absorbing fiber of this embodiment will be described. Since the method for producing the infrared absorbing fiber of this embodiment can produce the infrared absorbing fiber already described, the description of the matters already described will be omitted.
[0180] The method for producing an infrared absorbing fiber of the present embodiment may include an infrared absorbing fiber production step of preparing an infrared absorbing fiber containing fibers and infrared absorbing particles.
[0181] The infrared absorbing particles and fibers have already been explained, so a detailed explanation will be omitted here.
[0182] In the process for producing infrared absorbing fibers, specifically, for example, infrared absorbing particles can be disposed in one or more locations selected from the surface and the interior of the fibers.
[0183] The method for disposing the infrared absorbing particles in one or more locations selected from the surface and the inside of the fiber is not particularly limited. For example, any of the following methods (a) to (d) can be used. (a) A method in which infrared absorbing particles are mixed into the raw polymer of synthetic fibers and then spun into yarn. (b) A method in which a master batch is produced in advance by incorporating a high concentration of infrared absorbing particles into a portion of the raw polymer, and the master batch is diluted and adjusted to a specified concentration at the time of spinning before being spun. (c) A method in which infrared absorbing particles are dispersed in a raw material monomer or oligomer solution to prepare a dispersion in advance, and then a target raw material polymer is synthesized using the dispersion, and the infrared absorbing particles are simultaneously dispersed in the raw material polymer, followed by spinning. (d) A method in which infrared absorbing particles are attached to the surface of fibers obtained by prior spinning using a binder or the like.
[0184] Here, the above methods (a) to (d) will be further explained by giving specific examples. Method (a): An example in which polyester fibers are used as the fibers will be described.
[0185] First, the infrared absorbing particle dispersion is added to polyethylene terephthalate resin pellets, which is a thermoplastic resin, and the mixture is mixed uniformly in a blender, after which the solvent is removed. The mixture from which the solvent has been removed is melt-kneaded in a twin-screw extruder to obtain a master batch containing infrared absorbing particles. The obtained master batch is melt-mixed near the melting temperature of the resin, and spun, for example, by various known methods, to produce infrared absorbing fibers.
[0186] The method for producing the master batch is not particularly limited. For example, a mixture in which the infrared absorbing particles are dispersed in the thermoplastic resin can be prepared by melt-mixing the infrared absorbing particle dispersion liquid, the thermoplastic resin powder or pellets, and other additives as necessary, using a kneader while removing the solvent.
[0187] The kneading machine is not particularly limited, and one or more types selected from mixers such as a ribo blender, a tumbler, a Nauter mixer, a Henschel mixer, a super mixer, and a planetary mixer, a Banbury mixer, a kneader, a roll, a kneader-ruder, a single-screw extruder, and a twin-screw extruder can be used.
[0188] The method for preparing the mixture in which the infrared absorbing particles are dispersed in the resin is not limited to the above-mentioned form.
[0189] For example, after preparing an infrared absorbing particle dispersion, first, the dispersion medium of the dispersion is removed by a known method. Then, the powder obtained by removing the dispersion medium, powder particles or pellets of a thermoplastic resin, and other additives as necessary are uniformly melt-mixed to produce a mixture in which infrared absorbing particles are dispersed in a thermoplastic resin. In addition, a method of directly adding infrared absorbing particles to a thermoplastic resin and melt-mixing the mixture to produce a mixture in which infrared absorbing particles are dispersed in a thermoplastic resin can also be used.
[0190] A mixture of the infrared absorbing particles obtained by the above-mentioned method and a thermoplastic resin is kneaded in a vented single-screw or twin-screw extruder and processed into pellets, thereby obtaining a master batch containing the infrared absorbing particles. Method (b): A master batch containing infrared absorbing particles is prepared by utilizing a method similar to that of (a), etc. Then, the master batch and a master batch made of polyethylene terephthalate to which infrared absorbing particles are not added are melt-mixed at a desired mixing ratio near the melting temperature of the resin, and spun according to a known method to produce an infrared absorbing fiber. Method (c): For example, a case where urethane fibers are used as the fibers will be described.
[0191] A polymer diol containing infrared absorbing particles is reacted with an organic diisocyanate in a twin-screw extruder to synthesize an isocyanate-terminated prepolymer, which is then reacted with a chain extender to produce a polyurethane solution (raw polymer). The polyurethane solution is spun according to various known methods to produce infrared absorbing particles. Method (d): For example, a case where infrared absorbing particles are attached to the surface of natural fibers will be described.
[0192] First, a treatment liquid is prepared by mixing infrared absorbing particles, one or more binder resins selected from acrylic, epoxy, urethane, and polyester, and a solvent such as water.
[0193] Next, the natural fibers are immersed in the prepared treatment solution, or the natural fibers are impregnated with the prepared treatment solution by padding, printing, spraying, or the like, and then dried. In this way, the infrared absorbing particles can be attached to the natural fibers. The method (d) can be applied to any of semi-synthetic fibers, regenerated fibers, inorganic fibers, or blends, doubling, and blends thereof, in addition to the above-mentioned natural fibers.
[0194] The method for preparing the dispersion liquid of infrared absorbing particles that can be used when carrying out the above-mentioned methods (a) to (d) is not particularly limited, and for example, the dispersion liquid of infrared absorbing particles can be prepared by the method already described above.
[0195] In addition, the dispersion medium of the infrared absorbing particle dispersion liquid is not particularly limited and can be selected depending on the fibers to be mixed. For example, various general organic solvents such as alcohols, ethers, esters, ketones, and aromatic compounds, water, etc. can be suitably used.
[0196] When the infrared absorbing particles are attached to or mixed with fibers or the raw material polymers, the dispersion liquid of the infrared absorbing particles can be directly mixed with the fibers or the raw material polymers. If necessary, the pH may be adjusted by adding an acid or an alkali to the infrared absorbing particle dispersion liquid, and various surfactants, coupling agents, etc. may be added to further improve the dispersion stability of the infrared absorbing particles.
[0197] As described above, the infrared absorbing fiber of this embodiment contains fibers and infrared absorbing particles, and the infrared absorbing particles have a neutral color tone. Therefore, it is possible to make the infrared absorbing fiber have a neutral color tone. In addition, since the infrared absorbing particles contain composite tungsten oxide particles, the infrared absorbing fiber of this embodiment can be a fiber with excellent heat retention. As a result, the design of the textile product using the infrared absorbing fiber is not impaired, and it can be colored in complementary colors or light colors.
[0198] The infrared absorbing fiber of this embodiment can be used in various applications, such as textile products that require heat retention, such as cold weather clothing, sports clothing, stockings, curtains, and other industrial textile products. [Textile products] The textile product of the present embodiment is produced by processing the infrared absorbing fiber described above, and may contain the infrared absorbing fiber described above. Note that the textile product of the present embodiment may also be composed of the infrared absorbing fiber described above. EXAMPLES
[0199] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. (1) Evaluation method First, the evaluation methods in the following Examples and Comparative Examples (hereinafter, Examples and Comparative Examples may be collectively referred to as "Experimental Examples") will be described. (1-1) Solar reflectance and solar absorptance The transmittance and reflectance of the fiber product samples manufactured in each experimental example for light with wavelengths of 300 nm to 2100 nm were measured using a spectrophotometer UH4150 manufactured by Hitachi, Ltd. Then, the solar reflectance and solar absorptance were calculated according to JIS A 5759 (2016). The solar absorptance was calculated from the following formula (1).
[0200] Solar absorptance (%) = 100% - solar transmittance (%) - solar reflectance (%) (1) (1-2) Average particle size The average particle size was measured using a particle size measuring device based on dynamic light scattering (ELS-8000 manufactured by Otsuka Electronics Co., Ltd.). From the obtained particle size distribution, the average particle size was calculated, which is the average particle size weighted by particle volume, and is the volume average particle size obtained by multiplying the diameter of each particle by the volume of the particle in the particle aggregate and dividing the sum by the total volume of the particles. (1-3) Color The color value of the textile product samples produced in each experiment, L * and b * was calculated based on JIS Z 8701 (1999) and JIS Z 8729 (2004) from the reflectance for light with wavelengths between 380 nm and 780 nm. The weighting coefficients used to calculate the color tone were those for a D65 light source and a viewing angle of 10 degrees. (1-4) Powder X-ray diffraction pattern Powder XRD (X-ray Diffraction) measurements were carried out using a benchtop XRD instrument, D2 PHASER (BRUKER). (2) Explanation of experimental conditions and procedures [Example 1] (Preparation of Composite Tungsten Oxide Particles) Powders of tungstic acid (H2WO4) and cesium carbonate (Cs2CO3) were weighed out in a ratio of Cs / W (molar ratio) = 0.33, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was heated under a supply of 5 volume % H2 gas with N2 gas as a carrier, and reduced at a temperature of 600°C for 1 hour, and then fired at 800°C for 30 minutes in a N2 gas atmosphere to obtain a composite tungsten oxide, Cs 0.33 The powder was measured by powder XRD and found to be Cs 0.33 It was confirmed that it consisted of a single phase of WO3 crystals. (Preparation of Composite Tungsten Oxide Particle Dispersion) Cs above 0.33 10% by mass of WO3 powder, 10% by mass of an acrylic polymer dispersant having an amine-containing functional group (an acrylic dispersant with an amine value of 48 mgKOH / g and a decomposition temperature of 250°C) (hereinafter also referred to as "dispersant a"), and 80% by mass of toluene were weighed out. These were loaded into a paint shaker containing 0.3 mmφZrO2 beads, and ground and dispersed for 10 hours to obtain a composite tungsten oxide particle dispersion (hereinafter referred to as "Cs 0.33 A WO3 particle dispersion was obtained. (Preparation of Group 5 Element Composite Oxide Particles) Sodium carbonate (Na2CO3) and niobium oxide (Nb2O5) powders were weighed out in a ratio of Na / Nb (molar ratio) = 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was fired in air at a temperature of 1000°C for 5 hours to obtain NaNbO3 powder. The powder was measured by powder XRD and confirmed to consist of a single phase of NaNbO3 crystals.
[0201] Strontium carbonate (SrCO3) and niobium oxide (Nb2O5) powders were weighed out in a ratio of Sr / Nb (molar ratio) = 1.25, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was sintered in air at a temperature of 1300°C for 15 hours to obtain Sr5Nb4O 15 The powder was measured by powder XRD and found to be Sr5Nb4O 15It was confirmed that the crystal consisted of a single phase.
[0202] NaNbO3, Sr5Nb4O 15 The powders of Na, Sr, and niobium (Nb) were weighed out in a ratio of Na / Sr / Nb (molar ratio) = 0.75 / 0.25 / 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was compressed into a pellet shape and then fired at a temperature of 1400°C for 5 hours in an argon atmosphere to obtain the Group 5 element composite oxide particles, Na 0.75 Sr 0.25 The powder was measured by powder XRD and found to be Na 0.75 Sr 0.25 It was confirmed that it consisted of a single phase of NbO3 crystals. (Preparation of Group 5 Element Composite Oxide Particle Dispersion) The above Na 0.75 Sr 0.25 10% by mass of NbO3 powder, 10% by mass of dispersant a, and 80% by mass of toluene were weighed. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 15 hours to obtain a Group 5 element composite oxide particle dispersion liquid (hereinafter, "Na 0.75 Sr 0.25 A NbO3 particle dispersion liquid was obtained. (Preparation of infrared absorbing particle dispersion) Cs 0.33 WO3 particle dispersion and Na 0.75 Sr 0.25 The NbO3 particle dispersion and the Cs contained in the dispersion 0.33 WO3 particles and Na 0.75 Sr 0.25 The mixture was thoroughly mixed so that the mass ratio of the NbO3 particles was 100:50, to obtain an infrared absorbing particle dispersion liquid.
[0203] The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion was measured and found to be 25 nm. (Infrared absorbing fibers, manufacturing of textile product samples) Toluene was removed from the infrared absorbing particle dispersion liquid using a spray dryer to obtain an infrared absorbing particle dispersion powder. The obtained infrared absorbing particle dispersion powder was added to polyethylene terephthalate resin pellets, which is a thermoplastic resin, and mixed uniformly in a blender, and then melt-kneaded and extruded in a twin-screw extruder, and the extruded strands were cut into pellets to obtain a master batch (hereinafter also referred to as "master batch A"). Master batch A contains 40% by weight of infrared absorbing particles, which are an infrared absorbing component. The content ratio of infrared absorbing particles in the master batch is shown in the "Infrared absorbing particle content ratio" column in Table 1.
[0204] The masterbatch A was melt-spun together with the polyester masterbatch, and then drawn to produce a polyester multifilament yarn, which is an infrared absorbing fiber according to Example 1. At this time, the mixing ratio of the masterbatch A to the polyester masterbatch, which is a raw material polymer, was determined so that the solar reflectance of the fiber product sample described below would be 8%. Note that the polyester masterbatch does not contain infrared absorbing particles, and polyethylene terephthalate resin is used as the polyester resin.
[0205] The obtained polyester multifilament yarn was cut to prepare polyester staples, which were then used to produce spun yarn, which was then used to obtain a fiber product sample according to Example 1 having heat retaining properties.
[0206] As described above, when the infrared absorbing fiber was produced, the solar reflectance of the produced textile product sample was adjusted to 8%. The solar reflectance of the textile product sample was adjusted to 8% when the infrared absorbing fiber was produced in all of the following Examples and Comparative Examples except Comparative Example 5.
[0207] The spectral characteristics of the fabric sample were measured, and the solar absorptance was calculated. The calculated solar absorptance was 49.5%. The color index of the fabric sample was calculated from the reflectance, and the L * =87.3, b *= -2.1, and it was confirmed that the color was bright and had a very weak blue color and a neutral tone. The results are shown in Table 1.
[0208] The "Evaluation" column for each measurement result in Table 1 indicates the solar absorptance, b * The evaluation is categorized into three levels: ◎ (very good), ○ (good), and × (bad). ◎ is the highest evaluation, and ○ and × are the lowest.
[0209] The evaluation criteria for solar absorptance were as follows: 47% or more was rated as ◎, 43% or more but less than 47% was rated as ○, and less than 43% was rated as ×.
[0210] b * The evaluation criteria were as follows: -1.0 to +10.0: ◎; -3.0 to less than -1.0: ○; and less than -3.0: ×. * The higher the rating, the more blue is suppressed and the more neutral the color tone is.
[0211] Next, the temperature increasing effect on the reverse surface of the fabric of the fabric sample was measured as follows.
[0212] In an environment of 20°C and 60% RH, light was irradiated from a distance of 30 cm from the fabric of the textile product sample using a solar spectrum lamp (Solar Simulator XL-03E50 modified by Ceric Co., Ltd.) The temperature of the back side of the fabric of the textile product sample, located opposite to the side irradiated with light, was measured at regular intervals (0 seconds, 30 seconds, 60 seconds, 180 seconds, 360 seconds, 600 seconds) from the start of light irradiation using a radiation thermometer (HT-11 by Minolta Co., Ltd.).
[0213] The evaluation results are shown in Table 2.
[0214] The "Evaluation" column for each measurement result in Table 2 was also classified into three levels: ◎ (very good), ○ (good), × (bad). Specifically, a textile product sample at 25°C was irradiated with light for 600 seconds using a solar spectrum lamp. If the temperature of the backside of the fabric was 46°C or higher, it was evaluated as ◎; if it was 44°C or higher but less than 46°C, it was evaluated as ○; if it was less than 44°C, it was evaluated as ×. [Examples 2 to 4] When preparing the infrared absorbing particle dispersion, Cs in the infrared absorbing particle dispersion 0.33 WO3 particles and Na 0.75 Sr 0.25 The mass ratio of the NbO3 particles was adjusted to the value shown in the "Mass Ratio" column of Table 1. 0.33 WO3 particle dispersion and Na 0.75 Sr 0.25 The mixing ratio with the NbO3 particle dispersion liquid was changed. For example, in the case of Example 2, Cs 0.33 WO3 particles:Na 0.75 Sr 0.25 Each dispersion was weighed and mixed so that the NbO3 particles (mass ratio) was 100:100.
[0215] Except for the above, the masterbatches, polyester multifilament yarns as infrared absorbing fibers, and spun yarns according to Examples 2 to 4 were produced under the same conditions and procedures as in Example 1.
[0216] Then, textile product samples according to Examples 2 to 4 having heat retaining properties were produced under the same conditions and procedures as in Example 1, except that the spun yarn produced in each Example was used.
[0217] The textile product samples obtained in each example were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 5] When producing the infrared absorbing fiber, nylon 6 resin pellets were used as the thermoplastic resin instead of polyethylene terephthalate resin pellets.
[0218] A master batch containing 30 mass % of infrared absorbing particles (hereinafter also referred to as "master batch E") was prepared under the same conditions and procedures as in Example 2, except for the above points.
[0219] As the masterbatch, Masterbatch E was used, and as the raw polymer, Nylon 6 masterbatch was used in place of the polyester masterbatch.
[0220] Except for the above, a nylon multifilament yarn, which is an infrared absorbing fiber of Example 5, was produced under the same conditions and procedures as in Example 1.
[0221] The resulting nylon multifilament yarn was cut to prepare nylon staples, which were then used to produce spun yarn, which was then used to obtain a fiber product sample according to Example 5 having heat retaining properties.
[0222] The obtained textile product samples were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 6] When the infrared absorbing fibers were produced, acrylic resin pellets were used as the thermoplastic resin instead of polyethylene terephthalate resin pellets.
[0223] A master batch containing 40 mass % of infrared absorbing particles (hereinafter also referred to as "master batch F") was prepared under the same conditions and procedures as in Example 2 except for the above points.
[0224] As the masterbatch, Masterbatch F was used, and as the raw polymer, an acrylic masterbatch was used in place of the polyester masterbatch.
[0225] Except for the above, an acrylic multifilament yarn, which is an infrared absorbing fiber of Example 6, was produced under the same conditions and procedures as in Example 1.
[0226] The obtained acrylic multifilament yarn was cut to prepare acrylic staples, which were then used to produce spun yarns, which were then used to obtain a fiber product sample according to Example 6 having heat-retaining properties.
[0227] The obtained textile product samples were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 7] (Preparation of Group 5 Element Composite Oxide Particles) NaNbO3 and Sr5Nb4O prepared in Example 1 15 The powders of Na, Sr, and niobium (Nb) were weighed out in a ratio of Na / Sr / Nb (molar ratio) = 0.5 / 0.5 / 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was compressed into a pellet shape and then fired in a vacuum at a temperature of 1400°C for 5 hours to obtain a Group 5 element composite oxide particle, Na 0.5 Sr 0.5 The powder was measured by powder XRD and found to be Na 0.5 Sr 0.5 It was confirmed that it consisted of a single phase of NbO3 crystals. (Preparation of Group 5 Element Composite Oxide Particle Dispersion) The above Na 0.5 Sr 0.5 10% by mass of NbO3 powder, 5% by mass of dispersant a, and 85% by mass of methyl isobutyl ketone were weighed. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 15 hours to obtain a Group 5 element composite oxide particle dispersion liquid (hereinafter, "Na 0.5 Sr 0.5 A NbO3 particle dispersion liquid was obtained. (Preparation of infrared absorbing particle dispersion) Cs 0.33 WO3 particle dispersion and Na 0.5 Sr 0.5 The NbO3 particle dispersion and the Cs contained in the dispersion 0.33 WO3 particles and Na 0.5 Sr 0.5 The NbO3 particles were mixed in a mass ratio of 100:50 to obtain an infrared absorbing particle dispersion. 0.33The WO3 particle dispersion liquid used was that prepared in Example 1.
[0228] The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion was measured and found to be 24 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, polyester multifilament yarn, and spun yarn according to Example 7 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used. In addition, a textile product sample according to Example 7 having heat retention properties was obtained under the same conditions and procedures as in Example 1, except that the obtained spun yarn was used.
[0229] The obtained textile product samples were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Examples 8 to 10] When preparing the infrared absorbing particle dispersion, Cs in the infrared absorbing particle dispersion 0.33 WO3 particles and Na 0.5 Sr 0.5 The mass ratio of the NbO3 particles was adjusted to the value shown in the "Mass Ratio" column of Table 1. 0.33 WO3 particle dispersion and Na 0.5 Sr 0.5 The mixing ratio with the NbO3 particle dispersion liquid was changed. For example, in the case of Example 8, Cs 0.33 WO3 particles:Na 0.5 Sr 0.5 Each dispersion was weighed and mixed so that the NbO3 particles (mass ratio) was 100:100.
[0230] Except for the above, the masterbatches, polyester multifilament yarns as infrared absorbing fibers, and spun yarns according to Examples 8 to 10 were produced under the same conditions and procedures as in Example 7.
[0231] Then, textile product samples according to Examples 8 to 10 having heat retaining properties were produced under the same conditions and procedures as in Example 1, except that the spun yarn produced in each Example was used.
[0232] The textile product samples obtained in each example were evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 11] (Preparation of Group 5 Element Composite Oxide Particles) Barium oxide (BaO) and niobium oxide (Nb2O5) powders were weighed out in a ratio of Ba / Nb (molar ratio) = 1.25, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was sintered in air at a temperature of 1400°C for 10 hours to obtain Ba5Nb4O 15 The powder was measured by powder XRD and found to be Ba5Nb4O 15 It was confirmed that the crystal consisted of a single phase.
[0233] Potassium niobate (KNbO3, manufactured by Kojundo Chemical Laboratory Co., Ltd.), Ba5Nb4O 15 The powders of K, Ba, and niobium (Nb) were weighed out in a ratio of K / Ba / Nb (molar ratio) = 0.33 / 0.67 / 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was compressed into a pellet shape and then fired at 1400°C for 6 hours in an argon atmosphere to obtain the group 5 element composite oxide particles, K 0.33 Ba 0.67 The powder was measured by powder XRD and found to be 0.33 Ba 0.67 It was confirmed that it consisted of a single phase of NbO3 crystals. (Preparation of Group 5 Element Composite Oxide Particle Dispersion) Above K 0.33 Ba 0.67 10% by mass of NbO3 powder, 5% by mass of dispersant a, and 85% by mass of methyl isobutyl ketone were weighed. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 15 hours to obtain a Group 5 element composite oxide particle dispersion liquid (hereinafter referred to as "K 0.33 Ba 0.67 NbO3 particle dispersion liquid) was obtained. (Preparation of infrared absorbing particle dispersion) Cs 0.33 WO3 particle dispersion and K 0.33 Ba 0.67 The NbO3 particle dispersion was subjected to the0.33 WO3 particles and K 0.33 Ba 0.67 The NbO3 particles were mixed in a mass ratio of 100:100 to obtain an infrared absorbing particle dispersion. 0.33 The WO3 particle dispersion used was that prepared in Example 1. The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion was measured and found to be 29 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn of Example 11 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used.
[0234] The above spun yarn was used to manufacture a textile product sample having heat retention properties according to Example 11. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 12] (Preparation of Group 5 Element Composite Oxide Particles) Sodium carbonate (Na2CO3), strontium carbonate (SrCO3), and divanadium pentoxide (V2O5) powders were weighed out in a ratio of Na / Sr / V (molar ratio) = 0.75 / 0.25 / 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was fired for 3 hours at 1400°C in a 3% hydrogen / 97% argon (molar ratio) mixed atmosphere to obtain Na 0.75 Sr 0.25 VO3 powder was obtained. The powder was measured by powder XRD and found to be Na 0.75 Sr 0.25 It was confirmed that it consisted of a single phase of VO3 crystals. (Preparation of Group 5 Element Composite Oxide Particle Dispersion) The above Na 0.75 Sr 0.25 10% by mass of VO3 powder, 5% by mass of dispersant a, and 85% by mass of methyl isobutyl ketone were weighed. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 15 hours to obtain a Group 5 element composite oxide particle dispersion (hereinafter referred to as "Na 0.75 Sr 0.25As a result, a VO3 particle dispersion was obtained. (Preparation of infrared absorbing particle dispersion) Cs 0.33 WO3 particle dispersion and Na 0.75 Sr 0.25 The VO3 particle dispersion was treated with Cs 0.33 WO3 particles and Na 0.75 Sr 0.25 The mass ratio of the VO3 particles was 100:100 to obtain an infrared absorbing particle dispersion. 0.33 The WO3 particle dispersion used was that prepared in Example 1. The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion was measured and found to be 33 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn of Example 12 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used.
[0235] The spun yarn was then used to manufacture a textile product sample having heat retention properties according to Example 12. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 13] (Preparation of Group 5 Element Composite Oxide Particles) Sodium carbonate (Na2CO3) and tantalum oxide (Ta2O5) powders were weighed out in a ratio of Na / Ta (molar ratio) = 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was fired in air at a temperature of 800°C for 48 hours, and then heated from 800°C to 1200°C and fired for another 48 hours to obtain NaTaO3 powder. The powder was measured by powder XRD and confirmed to be composed of a single phase of NaTaO3 crystals.
[0236] Strontium carbonate (SrCO3) and tantalum oxide (Ta2O5) powders were weighed out in a ratio of Sr / Ta (molar ratio) = 1.25, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was fired in an air atmosphere at a temperature of 800°C for 48 hours, and then heated to 1200°C and fired for another 48 hours to obtain Sr5Ta4O 15 The powder was measured by powder XRD and found to be Sr5Ta4O 15 It was confirmed that the crystal consisted of a single phase.
[0237] NaTaO3, Sr5Ta4O 15 Powders of tantalum (Ta) and Sr were weighed out in a ratio of Na / Sr / Ta (molar ratio) = 0.8 / 0.2 / 1.0, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was compressed into a pellet shape and then sealed in a tantalum tube in an argon atmosphere. The sealed sample was subjected to a firing treatment at a temperature of 1400°C for 20 hours to obtain the Na 0.8 Sr 0.2 TaO3 powder was obtained. The powder was measured by powder XRD and found to be Na 0.8 Sr 0.2 It was confirmed that it consisted of a single phase of TaO3 crystals. (Preparation of Group 5 Element Composite Oxide Particle Dispersion) The above Na 0.8 Sr 0.2 10% by mass of TaO3 powder, 5% by mass of dispersant a, and 85% by mass of methyl isobutyl ketone were weighed out. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 15 hours to obtain a Group 5 element composite oxide particle dispersion liquid (hereinafter, "Na 0.8 Sr 0.2 TaO3 particle dispersion liquid) was obtained. (Preparation of infrared absorbing particle dispersion) Cs 0.33 WO3 particle dispersion and Na 0.8 Sr 0.2 The TaO3 particle dispersion liquid was 0.33 WO3 particles and Na 0.8 Sr 0.2The TaO3 particles were thoroughly mixed so that the mass ratio was 100:25 to obtain an infrared absorbing particle dispersion. 0.33 The WO3 particle dispersion used was that prepared in Example 1. The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion was measured and found to be 30 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn of Example 13 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used.
[0238] The spun yarn was then used to manufacture a textile product sample having heat retention properties according to Example 13. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 14] (Preparation of Composite Tungsten Oxide Particles) Powders of tungstic acid (H2WO4) and rubidium carbonate (Rb2CO3) were weighed out in a ratio of Rb / W (molar ratio) = 0.33, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was heated under a supply of 5 volume % H2 gas with N2 gas as a carrier, and reduced at a temperature of 600°C for 1 hour, and then fired at 800°C for 30 minutes in a N2 gas atmosphere to obtain a composite tungsten oxide, Rb 0.33 WO3 powder was obtained. The powder was measured by powder XRD and found to be Rb 0.33 It was confirmed that it consisted of a single phase of WO3 crystals. (Preparation of Composite Tungsten Oxide Particle Dispersion) Rb 0.33 20% by mass of WO3 powder, 10% by mass of dispersant a, and 70% by mass of methyl isobutyl ketone were weighed. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 10 hours to obtain a composite tungsten oxide particle dispersion (hereinafter referred to as "Rb 0.33 A WO3 particle dispersion was obtained. (Preparation of infrared absorbing particle dispersion) Rb 0.33 WO3 particle dispersion and Na0.5 Sr 0.5 The NbO3 particle dispersion liquid was subjected to 0.33 WO3 particles and Na 0.5 Sr 0.5 The mass ratio of NbO3 particles was 100:150 to obtain an infrared absorbing particle dispersion liquid. The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion liquid was measured and found to be 23 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn of Example 14 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used.
[0239] The above spun yarn was used to manufacture a textile product sample having heat retention properties according to Example 14. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Example 15] (Preparation of Composite Tungsten Oxide Particles) Powders of tungstic acid (H2WO4) and potassium carbonate (K2CO3) were weighed out in a ratio of K / W (molar ratio) = 0.33, and then thoroughly mixed in an agate mortar to obtain a mixed powder. The mixed powder was heated under a supply of 5 volume % H2 gas with N2 gas as a carrier, and reduced at a temperature of 550°C for 1.5 hours, and then fired at 800°C for 30 minutes in a N2 gas atmosphere to obtain a composite tungsten oxide, K2CO3. 0.33 WO3 powder was obtained. The powder was measured by powder XRD and found to be K 0.33 It was confirmed that it consisted of a single phase of WO3 crystals. (Preparation of Composite Tungsten Oxide Particle Dispersion) K 0.33 20% by mass of WO3 powder, 10% by mass of dispersant a, and 70% by mass of methyl isobutyl ketone were weighed. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 10 hours to obtain a composite tungsten oxide particle dispersion (hereinafter referred to as "K 0.33 A WO3 particle dispersion was obtained. (Preparation of infrared absorbing particle dispersion) K 0.33 WO3 particle dispersion and Na 0.5 Sr 0.5 The NbO3 particle dispersion was treated with K 0.33 WO3 particles and Na 0.5 Sr 0.5 The mass ratio of the NbO3 particles was 100:100 to obtain an infrared absorbing particle dispersion liquid. The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion liquid was measured and found to be 19 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn of Example 15 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used.
[0240] The above spun yarn was used to manufacture a textile product sample having heat retention properties according to Example 15. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Comparative Example 1] (Infrared absorbing fibers, manufacturing of textile product samples) As the infrared absorbing particle dispersion liquid, the Cs 0.33 A WO3 particle dispersion was used. A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn according to Comparative Example 1 were produced under the same conditions and procedures as in Example 1, except for the above points.
[0241] The above spun yarn was then used to manufacture a textile product sample having heat retention properties according to Comparative Example 1. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Comparative Example 2] (Infrared absorbing fibers, manufacturing of textile product samples) As the infrared absorbing particle dispersion liquid, the Na 0.75 Sr 0.25A NbO3 particle dispersion liquid was used. A master batch, a polyester multifilament yarn which is an infrared absorbing fiber, and a spun yarn according to Comparative Example 2 were produced under the same conditions and procedures as in Example 1, except for the above points.
[0242] The above spun yarn was then used to manufacture a textile product sample having heat retention properties according to Comparative Example 2. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Comparative Example 3] (Infrared absorbing fibers, manufacturing of textile product samples) As the infrared absorbing particle dispersion liquid, the Na 0.5 Sr 0.5 A NbO3 particle dispersion liquid was used. A master batch, a polyester multifilament yarn which is an infrared absorbing fiber, and a spun yarn according to Comparative Example 3 were produced under the same conditions and procedures as in Example 1, except for the above points.
[0243] The above spun yarn was then used to manufacture a textile product sample having heat retention properties according to Comparative Example 3. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2. [Comparative Example 4] (Preparation of iron oxide particle dispersion) 10% by mass of pigment powder made of iron oxide (Fe2O3) (TM Red 8270 manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd.), 5% by mass of dispersant a, and 85% by mass of methyl isobutyl ketone were weighed out. These were loaded into a paint shaker containing 0.3 mmφ ZrO2 beads, and ground and dispersed for 6 hours to obtain an iron oxide particle dispersion. (Preparation of infrared absorbing particle dispersion) Cs 0.33 The WO3 particle dispersion and the iron oxide particle dispersion were mixed with the Cs 0.33 The WO3 particles and the iron oxide particles were mixed at a weight ratio of 100:15 to obtain an infrared absorbing particle dispersion liquid. The average particle size of the infrared absorbing particles contained in the infrared absorbing particle dispersion liquid was measured and found to be 36 nm. (Infrared absorbing fibers, manufacturing of textile product samples) A master batch, a polyester multifilament yarn as an infrared absorbing fiber, and a spun yarn according to Comparative Example 4 were produced under the same conditions and procedures as in Example 1, except that the prepared infrared absorbing particle dispersion liquid was used.
[0244] The above spun yarn was then used to manufacture a textile product sample having heat retention properties according to Comparative Example 4. The obtained textile product sample was evaluated in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.
[0245] [Table 1]
[0246] [Table 2] (3) Evaluation results The textile product samples using the filament yarns, which are infrared absorbing fibers according to Examples 1 to 15, exhibited excellent infrared absorbing properties, as shown in Table 1. In addition, the textile products using the infrared absorbing fibers according to Examples 1 to 15 had a neutral and bright color tone. Furthermore, as shown in Table 2, the fabric back surface temperature of each of the textile products according to the examples was found to be excellent in heat retention.
[0247] In contrast, in Comparative Example 1, in which the composite tungsten oxide particles were used alone, the color tone was disadvantageously bluish. Also, in Comparative Examples 2 and 3, in which the Group 5 element composite oxide particles were used alone, sufficient infrared absorption properties were not exhibited, and it was found that the fabric back surface temperature of each of the textile products according to the comparative examples was poor in heat retention.
[0248] In addition, in Comparative Example 4, which uses composite tungsten oxide particles and iron oxide particles that have visible light color-changing ability but no infrared absorbing properties and does not contain Group 5 element composite oxide particles, sufficient infrared absorbing properties were not exhibited. For this reason, it was found that the fabric back surface temperature of the textile product sample in Comparative Example 4 was poor in heat retention. [Explanation of symbols]
[0249] 10 Unit Cell 11 Octahedron 12. Void (tunnel) 13 Element M 20 Infrared absorbing fiber 21 Textiles 21A surface 21B Inside 22 Infrared absorbing particles 221 Composite tungsten oxide particles 222 Group 5 element composite oxide particles CA center axis
Claims
1. Fibers and Infrared absorbing particles, The infrared absorbing fiber, wherein the infrared absorbing particles contain at least composite tungsten oxide particles and Group 5 element composite oxide particles.
2. The Group 5 element composite oxide particles are An A1 element which is one or more elements selected from H and alkali metal elements; An A2 element which is one or more elements selected from Mg and alkaline earth metals; and B element, which is one or more elements selected from V, Nb, and Ta; When the amount of substance of the A1 element contained is x1, the amount of substance of the A2 element is x2, and the amount of substance of the B element is y, 2. The infrared absorbing fiber according to claim 1, comprising a complex oxide that satisfies the relationships: 0.002≦(x1+x2) / y≦1.5, 0.001≦x1≦1, and 0.001≦x2≦1.
3. 3. The infrared absorbing fiber according to claim 2, wherein the A1 element is one or more elements selected from the group consisting of H, Li, Na, K, Rb, and Cs.
4. 3. The infrared absorbing fiber according to claim 2, wherein the A2 element is one or more elements selected from the group consisting of Ca, Sr, and Ba.
5. The A1 element is one or more elements selected from Na and K, The A2 element is one or more elements selected from Ca, Sr, and Ba, The B element is one or more elements selected from Nb and Ta, 3. The infrared absorbing fiber according to claim 2, wherein the x1, the x2, and the y satisfy the relationship: 0.7≦(x1+x2) / y≦1.
0.
6. The composite tungsten oxide particles have the general formula: M x WO 3-y 6. The infrared absorbing fiber according to claim 1 , comprising a composite tungsten oxide represented by the formula: (wherein element M comprises at least one selected from the group consisting of K, Rb, Cs and Tl, and 0.15≦x≦0.33, 0<y≦0.46).
7. 6. The infrared absorbing fiber according to claim 1, wherein the average particle size of one or more types of particles selected from the composite tungsten oxide particles and the Group 5 element composite oxide particles is 0.1 nm or more and 100 nm or less.
8. The infrared absorbing fiber according to claim 1 , wherein the infrared absorbing particles are contained in an amount of 0.001% by mass or more and 80% by mass or less based on the solid content of the fiber.
9. The fiber further includes a far-infrared emitting material disposed at one or more locations selected from the surface and the interior of the fiber, 6. The infrared absorbing fiber according to claim 1, wherein the far-infrared emitting substance is contained in an amount of 0.001% by mass or more and 80% by mass or less based on the solid content of the fiber.
10. 6. The infrared absorbing fiber according to claim 1, wherein the fiber is one or more types selected from a fiber group consisting of synthetic fibers, semi-synthetic fibers, natural fibers, regenerated fibers, and inorganic fibers, and a mixed yarn obtained by blending, doubling, or mixing two or more types of fibers selected from the fiber group.
11. 11. The infrared absorbing fiber according to claim 10, wherein the synthetic fiber is one or more types selected from the group consisting of polyurethane fibers, polyamide fibers, acrylic fibers, polyester fibers, polyolefin fibers, polyvinyl alcohol fibers, polyvinylidene chloride fibers, polyvinyl chloride fibers, and polyether ester fibers.
12. 11. The infrared absorbing fiber according to claim 10, wherein the semi-synthetic fiber is at least one selected from the group consisting of cellulosic fibers, protein fibers, chlorinated rubber, and hydrochloric rubber.
13. 11. The infrared absorbing fiber according to claim 10, wherein the natural fiber is at least one type selected from the group consisting of vegetable fibers, animal fibers, and mineral fibers.
14. 11. The infrared absorbing fiber according to claim 10, wherein the regenerated fiber is one or more types selected from the group consisting of cellulose-based fibers, protein-based fibers, alginate fibers, rubber fibers, chitin fibers, and mannan fibers.
15. 11. The infrared absorbing fiber according to claim 10, wherein the inorganic fiber is at least one type selected from the group consisting of metal fiber, carbon fiber, and silicate fiber.
16. A textile product comprising the infrared absorbing fiber according to any one of claims 1 to 5.
Citation Information
Patent Citations
Thermally insulating conjugate fiber
JP1993239716A
Infrared-absorbing processed textile product and processing thereof
JP1996003870A
Near-infrared absorption processing of cellulose-based fiber structural product
JP1997291463A
Fiber with excellent thermic ray radiation
JP1999279830A
Near-infrared absorption fiber and textile product using the same
JP2006132042A